2008
DOI: 10.1186/1756-6606-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-CaMKII deficiency causes immature dentate gyrus, a novel candidate endophenotype of psychiatric disorders

Abstract: Elucidating the neural and genetic factors underlying psychiatric illness is hampered by current methods of clinical diagnosis. The identification and investigation of clinical endophenotypes may be one solution, but represents a considerable challenge in human subjects. Here we report that mice heterozygous for a null mutation of the alpha-isoform of calcium/calmodulin-dependent protein kinase II (alpha-CaMKII+/-) have profoundly dysregulated behaviours and impaired neuronal development in the dentate gyrus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
417
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 255 publications
(441 citation statements)
references
References 76 publications
(75 reference statements)
23
417
0
Order By: Relevance
“…Similar changes in GC functions and/or in the state of GC maturation have been demonstrated in mice disrupted for the gene encoding alpha-CaMKII (27), brain-derived neurotrophic factor (44), or the glutamate receptor subunit GluK2/GluR6 (10,45). The deficiency in either of these genes has been shown to cause substantial behavioral abnormalities (27,46,47), which supports the idea that the GC dematuration can potentially cause dysfunction of the adult hippocampus. On the other hand, the increased GC excitability caused by the dematuration may improve some pathological conditions, such as reduced GC activity in animals exposed to chronic stress (7).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Similar changes in GC functions and/or in the state of GC maturation have been demonstrated in mice disrupted for the gene encoding alpha-CaMKII (27), brain-derived neurotrophic factor (44), or the glutamate receptor subunit GluK2/GluR6 (10,45). The deficiency in either of these genes has been shown to cause substantial behavioral abnormalities (27,46,47), which supports the idea that the GC dematuration can potentially cause dysfunction of the adult hippocampus. On the other hand, the increased GC excitability caused by the dematuration may improve some pathological conditions, such as reduced GC activity in animals exposed to chronic stress (7).…”
Section: Discussionsupporting
confidence: 60%
“…fluoxetine on expression of potential GC-specific maturation markers, desmoplakin, tryptophan-2,3-dioxygenase, and interleukin-1 receptor type I, whose expression is restricted to dentate GCs (27) and increases with postnatal development similarly to calbindin (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This highly localized hippocampus-specific increase in D 1 -like ligand binding is in agreement with the lack of an increase in D 1 mRNA levels or D 1 -like ligand binding in the brain regions other than the hippocampus in most previous studies. We have previously demonstrated a similar marked increase in D 1 -like ligand binding that is restricted to the dentate gyrus and mossy fiber tract in mice heterozygous for a-calcium/calmodulin-dependent protein kinase II (Yamasaki et al, 2008). We have also shown that the dopaminergic modulation at the mossy fiber synapse is clearly enhanced in a subpopulation of mice lacking the schizophrenia susceptible gene dysbindin-1 (Kobayashi et al, 2011b).…”
Section: Discussionmentioning
confidence: 48%